Top Skills Honing for Today’s Accountants: a Literature Review - Joshi, Prem Lal; Dsouza, Suzan - (The Indonesian Journal of Accounting Research, 2024)
Employability abilities are becoming increasingly important in today's technologically sophisticated, globally integrated job markets. The departments' continued adoption of new technology, automation tools, and software will ultimately change the expectations of the accounting teams. With the assistance of prior literature, this essay examines the vital abilities and skills accountants should possess today. Today's accountants need to acquire the most cutting-edge skills for effective performance. The earlier studies, which drew their conclusions from literature published in the last 20 years, laid the groundwork for the fundamental knowledge and abilities that modern accountants must possess. The four main skill areas that comprise the whole skill set needed by accountants in the modern workplace are business skills, soft skills, digital and technology skills, and ethical skills. It emphasizes how important it is to provide professional accountants with the most recent skill sets available so they may perform efficiently in a dynamic workplace. Accounting professionals must learn to use new technologies to continue in their field. The study suggests a theoretical framework by classifying twenty-three skills into four main categories: business, soft, ethical, and technology and digital skills. Future research directions are also suggested